MEMBANGUN KARAKTER SISWA PENDIDIKAN DASAR MUHAMMADIYAH MELALUI IDENTIFIKASI IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH - Utami, Ratnasari Diah (Universitas Muhammadiyah Surakarta, 2015)
he general objective of this research is to describe the general character educationimplementation applied in SD Muhammadiyah Baturan Karanganyar This research isdescriptive qualitative study. The sources of the research data consists of the informant, places(events), and document. Data collection technique used in this study were (1) observations(2) in-depth interviews with teachers, parents and students of SD Muhammadiyah BaturanKaranganyar. (3) Documentation. To test the validity of the data used triangulation of data andinformants. Analysis using the interactive analysis techniques that includes four components:data collection, data reduction, data display, and conclusion. The results ofthis researchis: Teachers in SD Muhammadiyah Baturan have attempted to prepare learning model ofcharacter, but have not had the right model to reinforce character education to students.Â character, education, primary education